Globalization, Erosion of Tax Base, and the Revenue Potential of Developing Asia's Foreign Exchange Reserve Build-Up - Donghyun Park (Asian Development Bank (ADB), 2008)
A major side effect of globalization is the erosion of the tax base due to the growing mobility of capital and the consequent international tax competition for capital. The potential loss of revenues is encouraging developing Asia's governments to look for alternative, nonconventional, nontax sources of revenue. The central objective of this paper is to explore the extent to which one potential source of nonconventional revenue - the region's soaring excess foreign exchange reserves - can help to compensate regional governments for the erosion of their tax bases. The analysis indicates that more active management of excess reserves along the lines of profit-maximizing sovereign wealth funds can indeed make a significant contribution to the region's nonconventional fiscal revenues.
hdl:11540/1777
Keywords: 330; Globalisierung; Steuerwettbewerb; Besteuerungsverfahren; Steuereinnahmen; Öffentliche Einnahmen; Währungsreserven; Asien